Sunday
April 20, 2014

Search: 14x^5y^4+21x^3y^2 divided by 7x^3y

Number of results: 15,658

Math
You handle it like an alg problem. subtract 2x from each side. 3y>-2x divide by 3 y>-2/3 x that is it. Only one thing you have to be worried about, if you multiply or divide by a negative number, the inequality changes: example 2x-3y>15 -3y>15-2x and here we divide...
Thursday, October 18, 2007 at 9:41pm by bobpursley

algebra
simplify and write using only positive exponents. thanks. (2x^3y^4)^-2 divided by (8xy^6)^-3
Wednesday, May 25, 2011 at 7:42pm by kristin

Calculus
Let x and y be the two side lengths of the full rectangle. The length x will be divided in two. The total lengths of fence needed will be L = 2x + 3y. You know that x y = 5,189,400 ft^2 dL/dx = d/dx (2x + 3*5,189,400/x) = 2 - 15,568,200/x^2 = 0 at minimum L x^2 = 7,784,100 x...
Monday, June 22, 2009 at 12:58am by drwls

algebra 2
I am trying to factor the expression -8y^2+28y-60 but can't get an answer that is correct. Here is an example of how the problem is supposed to be factored. If you have 21x2-77x-28 the first thing you would do is (21x )(x ). Next you would find two numbers that multiplied ...
Sunday, September 8, 2013 at 3:01pm by Kylee

trig
2r - 3r sin€ = 6 2sqrt(x^2 + y^2) - 3y = 6 2sqrt(x^2 + y^2) = 3y + 6 =3(y+2) 4(x^2 + y^2) = 9(y + 2)^2
Wednesday, March 2, 2011 at 3:53am by agrin04

Math
slope = (2 + 2)/(5 - 2) = 4/3 y-2 = (4/3)(x-5) 3y - 6 = 4x - 20 4x - 3y = 14
Saturday, April 7, 2012 at 9:23pm by Reiny

Intermediate Algebra
(6xy)^-3 = 1 / (6xy)^3 = 6^3x^3y^3 = 216x^3y^3.
Tuesday, June 19, 2012 at 9:27am by Henry

algebra
First line: x=3-3y 3y=3-x Divide with 3 y=1-x/3 y= -x/3 + 1 y=(-1/3)*x +1 Second line: x+3y= -6 3y= -6-x Divide with 3 y= -2 -x/3 y= -x/3 - 2 y= (-1/3)*x -2 The equation of a straight line is usually written this way: y = mx + b m = Slope or Gradient (how steep the line is) b...
Tuesday, May 31, 2011 at 4:32pm by Anonymous

Math
8x-3y=-6 >> 8x=-6/3y >> x=-6/24y then: 8(-6/24y)-3y=-6 (-6y/3)-3y=-6 (-6y-9y)/3=-6 -3y/3=-6 y=6 then: 8x-3*6=-6 8x-18=-6 8x=-6+18 8x=12 x=12/8=3/2 so: X=3/2, Y=6
Thursday, September 23, 2010 at 9:11am by LiNda

math
this is worse than before, now I have to read it as 21xy = -2 -49x^2 = 14 it can't be that, since the second equation clearly has no real solution. I have a feeling you meant to type 7x + 3y = -2 -7x + 7y = 14 but until you clarify the equation, there is no point in working it...
Monday, January 19, 2009 at 6:50pm by Reiny

Math
the form of the equation that most students seem to learn is y = mx + b, where m is the slope and b is the y-intercept. I will use a specific example. suppose you know the slope is -2/3 and the given point is (9,1) so y = -2/3 m + b but (9,1) lies on it, so 1 = (-2/3)(9) + b 1...
Thursday, October 2, 2008 at 4:55pm by Reiny

Math
1. 4(2-a)^2 -81 = 4(4-4a+a^2) -81 = 4a^2 - 16a + 16 -81 = 4a^2 - 16a - 65 = 2. -(x-y)^3 = -(x-y)^2(x-y) = -(x^2-2xy+y^2)(x-y) = -(x^3-x^2y-2x^2y-2xy^2+xy^2-y^3) = Combine like-terms: -(x^3-3x^2y-xy^2-y^3) = -x^3 + 3x^2y + xy^2 + y^3. 3. 3x^2 -27(2-x)^2 = 3x^2-27(4-4x+x^2) = 3(...
Monday, October 3, 2011 at 12:36am by Henry

Math
1. 4(2-a)^2 -81 = 4(4-4a+a^2) -81 = 4a^2 - 16a + 16 -81 = 4a^2 - 16a - 65 = 2. -(x-y)^3 = -(x-y)^2(x-y) = -(x^2-2xy+y^2)(x-y) = -(x^3-x^2y-2x^2y-2xy^2+xy^2-y^3) = Combine like-terms: -(x^3-3x^2y-xy^2-y^3) = -x^3 + 3x^2y + xy^2 + y^3. 3. 3x^2 -27(2-x)^2 = 3x^2-27(4-4x+x^2) = 3(...
Monday, October 3, 2011 at 12:36am by Henry

Trig
I am sure you meant 2/(y+2) + 3/y = -y/(y+2) common denominator is y(y+2), so multiply each term by that 2y + 3(y+2) = -y^2 2y + 3y + 6 = -y^2 y^2 + 5y + 6 = 0 (y+2)(y+3) = 0 y = -2 or y = -3 but y cannot be -2 or else we are dividing by zero, so x = -3
Tuesday, March 22, 2011 at 10:15pm by Reiny

Math Lit
Decide whether the pair lines is parallel,perpendicular 3x+5y=6 ,3x+3Y=10
Sunday, February 5, 2012 at 2:42pm by Anonymous

alg 2.
3lnxy-2ln2y = ln(x^3y^3) - ln(4y^2 = ln [(x^3y^3)/(4y^2)] = ln [(x^3y)/4]
Monday, May 19, 2008 at 7:32pm by Reiny

math
Write that as two equations. 2x + y = 11 55x + 3y = 11 Multiply the first equation by 3 and then subtract. 6x + 3y = 33 49x = -22 That leads to the value of x. Then use any equation for y. When you wrote 5 5x did you mean to write 5x or 55x? If you meant 5x + 3y = 11, then you...
Tuesday, October 30, 2007 at 8:14am by drwls

Physics
F(1x)=F(1)=10 N F(2x)=F(2)cos60=5•0.5=2.5 N F(2y) =F(2)sin60 = 5•0.866= 4.33 N F(3x) =- F(x)=- (10+2.5 )= -12.5 N F(3y) =- F(2y)= - 4.33 N F(3) = sqrt{ F(3x)²+F(3y)²} =13.23 N tan φ = F(3y)/F(3x) =4.33/12.5=0.364 φ = 19.1⁰ (south-west)
Saturday, May 25, 2013 at 8:23am by Elena

Math
a= x b = x+7 c = 13 x^2 + (x+7)^2 = 13^2 = x^2 + x^2 +7x +7x + 49 = 169 = 2x^2 + 14x + 49 = 169 = 2x^2 + 14x + 49 -169= 169-169 = 2x^2 + 14x -120 = 0 = x^2 +7x -60 = 0 (x -5)(x+12)= 0 x = 5 x = -12 ignored when it is negative a= 5 b = 12
Saturday, July 27, 2013 at 11:16pm by Chol

math
expand a simplify the first three terms of each binomial power a. (2z*3 - 3y*2)*5 b. (3b*2 - 2/b)*14 c. (5x*3 + 3y*2)*8 d. (sqrt.a + sqrt.5)*10 sqrt= square root
Tuesday, January 14, 2014 at 11:09pm by cathy

Algebra, please help quick
simlify the following to the lowest terms: (a) [x^2-y^2]/[x^2+y^2] (b) [3a^2+6ab-a-2b]/[9a^2-6a+1] (c) [x^4-y^4]/[x^3-y^3] (d) [36x^3y^4z]/[64x^5y^2z^3]
Tuesday, February 19, 2013 at 4:55am by Jeconiah

calculus
Evaluate the following line integral: ∮C[(4x^2+3x+5y)dx+(6x^2+5x+3y)dy] where C is the path around the square with vertices (0,0),(2,0),(2,2) and (0,2).
Tuesday, March 5, 2013 at 4:39pm by Anonymous

calculus
Evaluate the following line integral: ∮C[(4x^2+3x+5y)dx+(6x^2+5x+3y)dy] where C is the path around the square with vertices (0,0),(2,0),(2,2) and (0,2).
Tuesday, March 5, 2013 at 10:57pm by Anonymous

bobpursly,.math
Ok, assume it equals zero. 2x + 3y -6=0 subtract 3y from each side. add six to each side. divide both sides by two. its how its in the book i'm suppost to solve for x. but how? How do I solve for the following: Directions solve each literal equation for the individual variable...
Tuesday, December 19, 2006 at 9:29am by bobpursley

math
it usually takes two steps, 1. "move" all terms except the y term to the right side ---> -y = -7x + 7 2. divide each term by the coefficient of the y term ---> divide by -1 y = 7x - 7 #2. 15x + 3y + 2 = 9x + 14 - try it using my 2-step method
Tuesday, January 28, 2014 at 8:45pm by Reiny

math
first get rid of that useless mixed fraction. -7x-24=-79/3 now multiply each term by -3 to get rid of fractions and all those negative signs 21x + 72 = 79 21x = 7 x = 7/21 = 1/3
Wednesday, August 10, 2011 at 12:58am by Reiny

MATH
to Eliminate x x - y = -1 3x + 5y = 21 multiply (x - y = -1) by -3 -3x + 3y = 3 3x + 5y = 21 add both equations 0 + 8y = 24 8y = 24 y = 3
Thursday, January 13, 2011 at 7:49pm by helper

math
Common denominator = 35y: 3x/5y + 1/7 = (21x + 5y) / 35y.
Monday, October 18, 2010 at 3:31pm by Henry

Lines and Slopes Math
A line is perpendicular to x+3y-4=0 and has the same y-intercept as 2x+5y-20=0. Find an equation for the line
Thursday, January 6, 2011 at 11:46pm by Mathew

Intermediate Algebra
Simplify the following exponents and rewrite it in an equivalent form with positive exponents..24x^3y^-3/72x^-5y^-1
Friday, March 30, 2012 at 9:43pm by sherry

Algebra 1 Answer Evaluation
Factor. 1. 30y^3 - 50y A: 10y(3y - 5y) 2. Factor a^2 - 5a^2 + 2a -10 by grouping. A: ?
Monday, March 24, 2014 at 6:06pm by Anonymous

Algebra
Solve the following system by graphing. If there isn't a unique solution to the system 5x-3y=-36 3x+5y=26
Monday, March 31, 2014 at 1:34pm by Shirley

Algebra II
<<I multiplied (7x)(7x) first and got x squared + 14x + 49.>> Well you did that wrong, as well as some other steps. (7x)^2 = 49x^2 The polynomial you wrote is (x+7)^2 5x^3*(7x)^2 = 5*49 x^5 = 245 x^5
Sunday, February 3, 2008 at 11:43am by drwls

Algebra
I am pretty sure this goes like this 4y+3=3y+x (i) 2x+4y=18 (ii) Rearrange (i) so that x=4y+3-3y Take (ii) and sub x it will become 2(4y+3-3y)+4y= 18 2(y+3)+4y =18 2y+6+4y=18 6y+6=18 6y=18-6 6y=12 y=12/6 y=2 (iii) Now use what you found for y in (iii) and sub in the (ii or i ...
Friday, February 22, 2013 at 9:21pm by Alex

algerbra!
7(n+1)-4n=4 7n + 7 - 4n = 4 3n = -3 n = -1 -7(x-3)=-14 -7x + 21 = -14 -7x = -35 x=5 8=3+5(y-2) 8 = 3 + 5y - 10 15=5y y=3 2(x-3)+3(x-1)=-5 2x -6 + 3x - 3 = -5 5x = 4 x= 4/5
Monday, September 15, 2008 at 9:24pm by Anonymous

Pre-calculus
y = (-3x+2) / (2x-1), x = (-3y+2) / 2y-1), Cross multiply: -3y + 2 = 2xy-x, -3y - 2xy = -x-2, y(-3-2x) = -x -2, y = (-x-2) / (-2x-3). -2x-3 = 0, -2x = 3, X = -3/2. Domain = All real values of X except -3/2. Range = All values of y resulting from inputs (x) within the domain. -...
Sunday, December 4, 2011 at 6:25pm by Henry

Algebra: please check
There are several ways to write the equation of a straight line. The way troy showed you is the y-intercept-slope form. Your starting equation suggests that you have learned the point-slope form continue from y-2=1/3(x-1) by multiplying both sides by 3 to avoid fractions ... ...
Tuesday, June 8, 2010 at 12:10am by Reiny

Algebra
First factor out y. y(3y^2+15y+18) What multiplies to give you 18 and adds to give you 15? y(3y+6)(y+3) I hope this helps.
Thursday, March 11, 2010 at 8:13pm by PsyDAG

10th grade
If you have a graphing calculator just plug in y= (-4/3)x+(4/3) 4x+3y=4 -4x -4x 3y = -4x+ /3 /3 y = (-4/3)x+(4/3) I used (parenthesis) to show fractions.
Wednesday, October 27, 2010 at 5:50pm by Nate

math
This question has been posted before. Was it by you? There is no solution because the two lines x + 3y = 7, and x + 3y = 8 are parallel and do not intersect. You have already added "no solution" to your question. So what are you asking it?
Wednesday, January 7, 2009 at 9:04am by drwls

math
Replace x in the first equation with 3y + 4, and solve for y. First step: 3(3y +4) -2y = 2 Second step: 7y +12 = 2 Take it from there . The answers (x and y) are not integers
Monday, February 15, 2010 at 5:46pm by drwls

Algebra 1a
Solve the following system of equations. x+3y=6 x=8-3y What is the solution of the system? Type the ordered pair or indicate if there is no solution. Thank you very much
Wednesday, May 26, 2010 at 7:00pm by Nikki

algebra
6/y+2-4=y+20/3y+6 Multiply by 3y. 18 + 6y - 12y = 3 + 20 + 18y Combine y terms and numerical terms -5 = 24y Do you think you can take it from there?
Thursday, June 3, 2010 at 11:03pm by PsyDAG

alg2 help
[4x/ 3y]^2 it should look like 4x over 3y in parenthesis ^2 at the top right. please take me step by step I got 1.6
Sunday, July 14, 2013 at 8:55pm by tyneisha

math
to find the slop solve for y. so for 5x+3y=6 put the y terms on one side and them divide through by the coeficient of y. 3y=5x+6 -divide thru by 3 y=5/3x+2
Tuesday, April 21, 2009 at 10:40am by Riley

Math
first one: 3(2y-4)=9-3(y+1) 6y - 12 = 9 - 3y - 3 6y + 3y = 6+12 9y = 18 y = 2 2nd: (x+5)(x-3)=9 x^2 - 3x + 5x - 15 = 9 x^2 + 2x - 24 = 0 (x+6)(x-4) = 0 so x+6 = 0 or x-4 = 0 x = -6 or x = 4
Sunday, December 12, 2010 at 5:06pm by Reiny

Calculus
Hmm. I get y^3 + 2x^2 = 1 3y^2 y' + 4x = 0 y' = -4x/(3y^2) y(1) = -1, so y'(1) = -4/3 so, now you have a point (1,-1) and a slope: -4/3 y+1 = -4/3 (x-1) I assume that massaging that to slope-intercept form presents no problems...
Monday, April 1, 2013 at 2:22pm by Steve

Calc
I have 3 choices for that A 4x -3y + 25 = 0 B 4x + 3y - 25 = 0 C 3x + 4y -24 = 0 i dunno what is the correct answer
Monday, December 14, 2009 at 9:04am by Janice

Geometry
Find the measure of each side of isosceles triangle ABC with AB = BC if AB = 4y , BC = 3y + 2 , and AC = 3y.
Tuesday, October 19, 2010 at 10:40am by Rhonda

math
sorry. didn't see the first line. clear the fractions 15 + 3y = 5x and collect terms 5x - 3y - 15 = 0
Friday, September 23, 2011 at 12:57pm by Steve

algebra
from the 2nd: x = 3y+6 sub into 1st 9(3y+6) - 6y = -30 27y +54 - 6y = -30 21y = -84 y= -4 then x = 3(-4) + 6 = -6 x=-6 , y = -4
Monday, December 17, 2012 at 8:43pm by Reiny

College Algebra
What is the leading coefficient and degree in these two problems? 1). 4x^3y - 3xy^2 + x^2y^3 2). -x^5y + 2x^2y^2 + xy^4
Tuesday, October 2, 2007 at 1:08am by Courtney

Math
5s7t-7+9s+4t-6 9X-5Y-9X-6Y+10 5X2-3Y+8X2-6X+4Y i DON'T UNDERSTAND
Monday, January 11, 2010 at 8:17pm by Kaleigh

algebra 2
Identify the point of intersection listed below each system of linear equations that is the solution of that system. 2x+5y=10 x-3y=-6 (5,0);(0,2); (3,1)
Tuesday, January 4, 2011 at 1:04am by Misty

Math
Factor 1. a^4-16 2. (m-n)^2-(2m+3n)^2 3.2x^4y^4-6x^5y^3+8x^3y 4.12m^2n^3+18m^3n^2
Sunday, October 2, 2011 at 2:53am by Melissa

algebra ll
solve the system of equations 4x - 3y= 8 2x+ 5y= 9 thanks for the hint but i think the answer is (1/2,2) or(2,1) if wrong please reply bobpursley and show work so ican understand
Tuesday, August 12, 2008 at 7:11pm by adam

algebra
It would help if you proofread your questions before you posted them. I assume the top equation is -4x+3y = 3. Multiply that equation by 3. I assume the second equation is 7x + 9y = 6. -12x + 9y = 9 7x - 9y = 6 Add the two equations. -5x = 15 Take it from there.
Sunday, January 26, 2014 at 9:12pm by PsyDAG

Calculus Help Please!!! Urgent!!!
-6x/y^5 is not the answer 3x^2 - 3y^2 y' = 0 now use the quotient rule: y" = (2xy^2 - 2x^2y y')/y^4 = 2x(y-xy')/y^3 = 2x(y-x(x^2/y^2))/y^3 = 2x(y^3-x^3)/y^5 or, use implicit differentiation twice: x^3-y^3 = 3 3x^2 - 3y^2 y' = 0 6x - 6y(y')^2 - 3y^2y" = 0 y^2 y" = 2x - 2y(y')^2...
Wednesday, April 9, 2014 at 1:35pm by Steve

Math - PreCalc (12th Grade)
Use the inverse matrix to solve this system of equations: 4x+3y=7.5 7x+9z=14 4y-z=8.3 4,3,0 7,0,9 0,4,-1
Friday, March 21, 2014 at 9:20am by Shawna

math
1/(2y) + 3/(2x) = x/(2xy) + 3y/(2xy) = (x+3y)/(2xy) and now it's easy, eh?
Thursday, September 26, 2013 at 9:03pm by Steve

Algebra 2
Before I go on and give you the problenms let me explain. i am not some lazy kid trin to get people to do my homework over the internet. I am freshman that just recently skippeda garde in math and I need some help. The problems below are from my pop quiz out of the text book i...
Sunday, October 21, 2007 at 8:01pm by Allen

Algebra 2
Before I go on and give you the problenms let me explain. i am not some lazy kid trin to get people to do my homework over the internet. I am freshman that just recently skippeda garde in math and I need some help. The problems below are from my pop quiz out of the text book i...
Sunday, October 21, 2007 at 8:02pm by Allen

Math please help!!
Rewrite your system: y+2x=5 3y+x= -5 2x+y=5 x+3y= -5 In google type: solve system substitution When you see list of results click on: SolverSOLVE linear system by SUBSTITUTION When page be open in first roow type 2x+1y=5 In second roow type: 1x+3y= -5 and clic option Solve You...
Monday, February 28, 2011 at 6:34pm by Anonymous

algebra 2
same thing with 4. Eliminate z, then work with w,x,y add 1&2, subtract 3 from 2*1, add 1&4 to get 3w+3y = 3 3w+3y = 6 4w+2x+2y = 7 I can see a big problem already.
Wednesday, October 16, 2013 at 4:15pm by Steve

MATH
2X-3Y=5 -2X -2X -3Y=5-2X DIVIDE BOTH SIDES BY -3 Y=-5/3+2/3X NOW DO THE SAME FOR THE OTHER ONE PLUG THE -2 IN FOR X Y=-5/3+2/3(-2) PUT IN CALC WATCH SIGNS!! Y=-3
Monday, December 9, 2013 at 12:58pm by SAM

Math
What is 5+7x+2x-3+6 simplified, x+y+4x-3x+2y+3y simplified
Tuesday, September 6, 2011 at 5:12pm by Aaron

Math
Is this right I have to set it to y=? 3x-y=9: y=-9+3x How would you set these two problems to y=? 3y=x+6 4x+3y=12
Sunday, February 21, 2010 at 2:06pm by Ryan

geometry
3y + 2x + 12 = 0. y = mx + b, Solve the given Eq for y: 3y = -2x - 12, Divide both sides by 3: y = (-2/3)x - 4.
Monday, November 1, 2010 at 3:24pm by Henry

algebra
Simplify 5x^7y^6/ 4y^6x^3*7x^3y^4/6x^2y^5
Tuesday, February 3, 2009 at 10:39pm by kate

algebra
Simplify 5x^7y^6/ 4y^6x^3 * 7x^3y^4/6x^2y^5
Tuesday, February 3, 2009 at 10:39pm by kate

correct , math
Directions: Facotor each of the following polynomials completely. 14x ^2 -20x + 6 the answer that i got was: 7x^2-10x+3= (7x-3)(x-1) not quite. You left out the two, you just cant throw it away. 2(7x-3)(x-1) can you show me please the steps I am getting confused.
Friday, February 9, 2007 at 2:49am by jasmine20

Math (URGENT)
Expand and simplify. 12-2(3y-2)(3y+2)-(2y+5)(2y+5) Textbook Answer: -22y^2-20y-5 I don't know how to get that. Can someone show me the step by step process? thank you very much.
Thursday, April 22, 2010 at 11:07pm by John

math
DETER MINE THE PRODUCT OF THE FOLLOWING.1.(3Y+4X)(3Y-4X) 2.(p1/2Q)2 3.(A+BC)(2X-4B) 4.(X-1)(X2+2X+3) 5.(A+2B)(-3A2+2AB+2B2)
Tuesday, January 24, 2012 at 2:33pm by Anonymous

math
DETER MINE THE PRODUCT OF THE FOLLOWING.1.(3Y+4X)(3Y-4X) 2.(p1/2Q)2 3.(A+BC)(2X-4B) 4.(X-1)(X2+2X+3) 5.(A+2B)(-3A2+2AB+2B2)
Tuesday, January 24, 2012 at 2:40pm by Anonymous

Math 3
this is the easiest way based on the fact that for Ax + By + C = 0, the slope is -A/B slope of line is (6-5)/(4-1) = 1/3 so the equation must be x - 3y + c = 0 plug in (1,5) 1-15 + c = 0 c = 14 so x - 3y + 14 = 0 from there you can change it to any form that was asked for
Wednesday, May 2, 2012 at 7:51pm by Reiny

college Algebra
First you need to replace the x in the original equation with the given variable 48-7y 8(48-7y) + 3y = -40 384 -56y +3y=-40 -56y + 3y = -40 - 384 -53y = -424 -53y/-53=-424/-53 y=8 x=-8 Ordered pair (8,-8)
Wednesday, April 21, 2010 at 8:41pm by Mrs P

calculus
a) Assuming you meant x^3 + y^3 - x y^2 = 5 3x^2 + 3y^2 dy/dx - x(2y)dy/dx - y^2 = 0 dy/dx(3y^2 - 2xy) = y^2 - 3x^2 dy/dx = (y^2 - 3x^2)/(3y^2 - 2xy) b) just arithmetic, you do it c) yours d) for a horizontal tangent, dy/dx = 0 then y^2 - 3x^2 = 0 y^2 = 3x^2 y = ± x√3 ...
Wednesday, March 13, 2013 at 9:12pm by Reiny

Math 141
I am having trouble with this problem. perform the indicated operations and simpily the result as much as possible a) (3x - 2) (x^2 + 2x - 4 ) the answer i got so far is 3x^3 + 4x^2 -16x + 8. Am i done or i have to conitnue to simplify? if so, what do i need to do? b) 10x^3y^2...
Saturday, April 7, 2012 at 3:36pm by John Terry

math
Trial and error really for x and y being whole numbers. You have to see, for example, how many 2's [the 2x bit] to take away from 4 [on the RHS] before it's divisible by -3 [from the 3y bit] For example, from -3y = 4 - 2x x = 5 will give -3y = 6 which means y = -2 The best ...
Friday, March 20, 2009 at 7:52pm by GanonTEK

math algebra please help!
x + y = 670 and 7x + 5y = 3740. With two equations, you have enough information to solve for both x and y. Multiply both sides of the first equation by 7 7x + 7y = 4690 Subtract the previous equation from that 7x + 5y = 3740 _______________ 2y = 950 y = 475 x = 670 - 475 = 195
Monday, February 9, 2009 at 11:27pm by drwls

one more question1
can anyone please help me with understanding how to graph equations such as 2x-3y=9, 6x-5y+20=0, -2x=2y +5, and y=-2. Thnx!
Wednesday, February 11, 2009 at 8:01pm by anonymous

Algebra 1
cost of plain pizza --- x cost per topping -----y x + 3y = 15.25 x + 5y = 17.75 subtract them 2y = 2 continue .....
Wednesday, November 14, 2012 at 1:54pm by Reiny

Math
Can somebody please explain to me how to factor trinomials that contain two unknown variables and are complex sum & product?? Examples: 2x^2 + 13xy + 15y^2 11x^2 + 14xy + 3y^2 I understand how to factor trinomials that only have x as the variable, but please someone help with ...
Wednesday, April 4, 2007 at 7:04pm by Danielle

math
Thanks, it's much easier when you pin-point the problem! In general, the coefficients of x and y are not the same between the two equations. When you want to eliminate y, and the coefficients are not the same, you find the LCM (lowest common multiple) of the two coefficients ...
Monday, June 1, 2009 at 5:13pm by MathMate

math
solve for x and y when 5x-3y-2=0 and 7x+y=0. Please this is sooo hard. no clue how to do it. please show me how to do it.
Monday, February 16, 2009 at 12:38am by neil hannit

Math
gather up the y's on one side: 7x+3y = 19-10 10y = 9 y = 9/10
Wednesday, October 9, 2013 at 7:13pm by Steve

Algebra 1
-2x + y = 2 2x + 3y = 5 x + 2y = -13 9x +7y = -3 7x + 9y = -30
Thursday, November 21, 2013 at 10:26pm by Kuai

Pre-Algebra
1. 3w – 10w 13w –7w –7 7w 2. y + 2y +3z 2y + 3z 3y + 3z 2y2 + 3z 6yz 3. 6r + r – 5r 2r 1r + r 0r 7r – 5r 4. 5x + 2(x + 6) 7x + 6 7x2 + 12 7x + 12 7x (x + 6) 5. –3m + 3(m + 6) 6 –6m + 6 6m + 18 18
Monday, November 26, 2012 at 3:38pm by Jman

Math help :(
1. 3w – 10w 13w –7w –7 7w 2. y + 2y +3z 2y + 3z 3y + 3z 2y2 + 3z 6yz 3. 6r + r – 5r 2r 1r + r 0r 7r – 5r 4. 5x + 2(x + 6) 7x + 6 7x2 + 12 7x + 12 7x (x + 6) 5. –3m + 3(m + 6) (1 point)6 –6m + 6 6m + 18 18
Wednesday, December 18, 2013 at 3:21pm by Princess Anna

Math help
Can someone check my answers on these? Thank you!! Solve each system using addition or subtraction. 1. x+y=8 x-y=4 For the solution I got (6,3) 2. x-3y=7 x+2y=2 For the solution I got (4,-1) 3. 5s+2t=6 9s+2t=22 For the solution I got (-4,13) 4. 2x+3y=13 x-3y=2 For the ...
Thursday, January 23, 2014 at 6:44am by Anonymous

math
Help?Simplify each expression.1. 3w – 10w a. 13w b. –7w c. –7 d. 7w 2. y + 1.2y +1.2z a. 2.4yz b. 1.3y + 1.2z c. 1.2y2 + 1.2z d. 2.2y + 1.2z 3. 6r + r – 5r a. 2r b. 1r + r c. 0r d. 7r – 5r 4. 5x + 2(x + 6) a. 7x + 6 b. 7x2 + 12 c. 7x + 12 d. 7x (x + 6) 5. –3m + 3(m + 6) a. 6 b...
Friday, November 22, 2013 at 12:55pm by Anonymous

Calculus
x² - 2xy + y³ = c 2x - 2y - 2xy' + 3y² y' = 0 2(x-y) + y'(3y²-2x) = 0 y' = 2(y-x)/(3y²-2x)
Tuesday, October 4, 2011 at 11:32pm by Steve

Calculus
x^2 - 2xy + y^3 = C 2x - 2y - 2xy' + 3y^2 y' = 0 y'(3y^2 - 2x) = 2(y-x) y' = 2(y-x)/(3y^2 - 2x)
Monday, April 29, 2013 at 10:19pm by Steve

Algebra
easiest way: since the slope is -2/3, the equation must look like this: 2x + 3y = C plug in the point (-5,-5) -10 - 15 = c = -25 2x + 3y = -25 re-arrange if needed.
Sunday, October 20, 2013 at 10:23pm by Reiny

Pre-Calculus
since the line is perpendicular, their slopes are negative reciprocals of each other, that means, they must be OPPOSITE in sign so first slope = -3/2 2nd slope = +2/3 y-2 = (2/3)(x-4) 3y-6 = 2x-8 3y = 2x - 2 y = (2/3)x - 2/3
Tuesday, November 19, 2013 at 8:22am by Reiny

Math
3y+24/2y=9, multiply both sides by 2y, then you get 3y+24=18y..I think you can go from there
Thursday, July 22, 2010 at 11:29pm by Jen

math
Get rid of parenthesis. 2y+y^2-xy-xy+y-3y^2 Combine like terms. 3y - 2y^2 -2xy
Wednesday, August 3, 2011 at 11:09am by PsyDAG

math
steve, i still have two question I don't understand. 1. x=3y-2/4,what is the value of y in terms of x ? 2. x=y^3/3y^2+y/2,what is the value of y in terms of x ?
Sunday, January 13, 2013 at 2:27pm by gary

math
steve, i still have two question I don't understand. 1. x=3y-2/4,what is the value of y in terms of x ? 2. x=y^3/3y^2+y/2,what is the value of y in terms of x ?
Sunday, January 13, 2013 at 2:27pm by gary

Algebra 1
Okay. So I am completely lost with this... Any help would be great! 3. Solve the system using any method – graphing, substitution, or linear combination. Make sure to show your work. 2x + 5y= 8 x + 3y= 2
Thursday, January 10, 2013 at 11:04pm by Miranda

Pages: <<Prev | 1 | 2 | 3 | 4 | 5 | 6 | 7 | 8 | 9 | 10 | Next>>

Search
Members